A sulfur-doped coffee grounds biochar supported Cu-Co alloy catalyst, a preparation method and application thereof

CN118204095BActive Publication Date: 2026-10-23HENAN POLYTECHNIC UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410305960.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-18
Publication Date
2026-10-23
Estimated Expiration
2044-03-18

AI Technical Summary

Technical Problem

然而,LDH衍生催化剂的比表面积和孔隙结构并不突出,会对催化反应中的传质过程和活性位点的暴露产生负面影响

Benefits of technology

[0022]生物炭是一种可再生碳材料,可从水稻壳、玉米秸秆、柚子皮、花生壳、核桃壳等可再生生物质中生产出来,与其他生物质相比,从咖啡残渣中提取的生物炭材料通常具有优于从其他生物质中提取的生物炭材料的物化性能,这是因为在咖啡豆的烘焙及咖啡制备过程中,其内部的分子(如咖啡因、单宁酸、多酚等)会逸出并在咖啡渣内部形成均匀分布的孔隙,有利于储存活化剂(如H2SO4),使制备的生物炭材料具有较高的比表面积和孔隙体积;另外,被硫酸活化的咖啡渣生物炭表面通常富含含氧官能团(如-OH、-CO、-COOH、-COO-等),这些官能团可作为LDH的成核中心,此外,生物炭被硫酸活化后,硫原子可以掺杂到咖啡渣生物炭骨架(SCB)中,在热处理过程中可以通过强的金属-硫键作为金属锚定点,进一步使金属原子能够很好地分散在咖啡生物炭上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118204095B_ABST
    Figure CN118204095B_ABST
Patent Text Reader

Abstract

The present application relates to the chemical technology field, specifically a kind of sulfur-doped coffee grounds biochar supported Cu-Co alloy catalyst and its preparation method and application, the present application is synthesized by in-situ growth method by Cu-Co-Al is supported on SCB skeleton Layered nanostructure precursor, by the controllable reduction of precursor finally obtains Cu-Co-Al / SCB catalyst, Cu-Co-Al is grafted to SCB and promotes the electron transfer of Cu to Co, lead to the formation of Cu-Co alloy, there is very strong interaction between the two, the electron interaction between Cu and Co is conducive to the selective conversion of biomass furfural to cyclopentanol, in the catalytic reaction process, it is beneficial to mass transfer and expose more easily accessible active site, so as to improve the catalytic performance of catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of chemical technology, specifically to a sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst, its preparation method, and its application. Background Technology

[0002] The increasing depletion of fossil resources and their impact on climate have presented humanity with the challenges of an energy crisis and environmental pollution. To address these issues, utilizing abundant renewable biomass and its derivatives as chemical feedstocks to produce high-value chemicals and fuels is a promising option for alleviating energy shortages. Furfural, derived from lignocellulose, is an important biomass platform molecule and a typical α,β-unsaturated compound. It can be further converted into various high-value-added downstream products such as furfuryl alcohol (FFA), cyclopentanone (CPO), cyclopentanol (CPL), tetrahydrofurfural alcohol (THFA), 2-methylfuran (2-MF), and pentanediol through several transformation pathways, including hydrogenation, rearrangement, hydrogenolysis, and ring-opening. Among these value-added products, cyclopentanol is an important intermediate in the synthesis of pesticides, rubber chemicals, fungicides, and pharmaceuticals.

[0003] In current industrial processes, cyclopentanol is typically produced via the oxidation of cyclopentene or the decarboxylation of adipic acid and its derivatives. These processes use non-renewable petrochemical products as feedstocks, inevitably generating substantial amounts of solid waste. Therefore, there is an urgent need to develop a green and sustainable route for the synthesis of cyclopentanol. The aqueous-phase catalytic hydrogenation rearrangement of biomass-derived furfural to cyclopentanol may be a feasible route. However, considering the multiple steps involved in the conversion from furfural to cyclopentanol, selectively obtaining cyclopentanol under mild conditions presents significant challenges. Therefore, it is necessary to design a highly selective, low-cost catalyst for the directed synthesis of cyclopentanol from furfural.

[0004] In recent years, many supported transition metal catalysts have been applied to the catalytic hydrogenation rearrangement of furfural to cyclopentanol. Among them, noble metal catalysts such as Pt, Pd, Ru, and Au have been extensively studied, and it has been found that they exhibit high catalytic activity and selectivity for cyclopentanol by suppressing side reactions. However, considering large-scale industrial applications, the high cost and scarcity of noble metals limit their widespread use. Therefore, researchers have devoted considerable effort to the development of alternative non-noble metal catalysts such as Co, Ni, and Cu. Co, Ni, and Cu have been reported to exhibit high catalytic activity in the hydrogenation of furfural, but controlling product selectivity still faces significant challenges. For example, Co and Ni-based catalysts generally exhibit high catalytic activity in the aqueous hydrogenation of furfural, but non-selective hydrogenation of the C=O and C=C double bonds in the furfural molecule always occurs, and the resulting tetrahydrofurfuryl alcohol byproduct eliminates the possibility of hydrogenation rearrangement of the intermediate furfuryl alcohol (a key intermediate in the formation of cyclopentanol). Compared to Co and Ni-based catalysts, Cu-based catalysts can selectively hydrogenate the C=O double bond in furfural, thereby generating the key intermediate furfuryl alcohol. However, due to the tendency of Cu to sinter or leach under reaction conditions, Cu-based catalysts often exhibit low catalytic activity and stability in the aqueous hydrogenation rearrangement of furfural. To overcome the problems faced by single-metal Co, Ni, and Cu catalysts, various bimetallic catalysts have been developed to suppress the high activity of Co and Ni-based catalysts in the non-selective hydrogenation of the C=C double bond on the furan ring in furfural, and to address the sintering or leaching of Cu in the aqueous phase. Although alloying with metals Co, Ni, or Cu can improve the selectivity and stability of single-metal catalysts, their catalytic activity, stability, and selectivity for cyclopentanol still need further improvement. Therefore, it remains essential to construct efficient and stable non-noble metal-based bimetallic catalysts for the directed catalytic conversion of furfural to cyclopentanol.

[0005] Over the past few decades, LDH (hydrotalcite)-derived catalysts have received considerable attention for catalytic hydrogenation. After heat treatment, mixed metal oxides (MMOs) with uniformly dispersed components can be formed and widely used in catalytic hydrogenation reactions. Furthermore, the electronic microenvironment of the metal in LDH-derived catalysts can be enhanced by the insertion of other divalent metal cations with similar atomic radii (such as Mg). 2+ Cu 2+ Co 2+ Ni 2+ Zn 2+ (e.g., regulation) can improve the catalytic activity and selectivity of the corresponding catalysts. However, the specific surface area and pore structure of LDH-derived catalysts are not outstanding, which can negatively affect the mass transfer process and the exposure of active sites in the catalytic reaction. Summary of the Invention

[0006] To address the shortcomings of the existing technologies, the present invention aims to provide a sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst, its preparation method, and its application. The present invention utilizes an in-situ growth method to construct a Cu-Co-Al catalyst precursor supported on an SCB framework, and prepares a Cu-Co-Al / SCB catalyst through controlled reduction. The Cu-Co alloy sites formed on the Cu-Co-Al / SCB catalyst are uniformly dispersed, exhibiting excellent catalytic performance for the aqueous hydrogenation rearrangement of cyclopentanol in the synthesis of furfural from biomass.

[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0008] A method for preparing a sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst includes the following steps:

[0009] Coffee grounds were mixed with sulfuric acid, stirred and dried, and then pyrolyzed and reduced in an inert atmosphere to obtain a solid powder. The solid powder was washed and dried to obtain sulfur-doped coffee grounds biochar.

[0010] Soluble cobalt salt, soluble copper salt, and soluble aluminum salt are dissolved in water and mixed with stirring to obtain solution A. NaOH and Na2CO3 are dissolved in water and mixed with stirring to obtain solution B.

[0011] The sulfur-doped coffee biochar was added to solution A and stirred to obtain a mixed solution. Solution B was added to the mixed solution to adjust the pH to 9-11, resulting in a suspension. The suspension was heated and stirred and aged. The precipitate was obtained by filtration. The precipitate was filtered and washed until the filtrate was neutral to obtain a filter cake. The filter cake was dried and then thermally reduced in a reducing atmosphere. After cooling to room temperature, it was passivated with a mixed gas to obtain a sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst.

[0012] In a preferred embodiment of the present invention, during the preparation of sulfur-doped coffee biochar, the mass ratio of coffee grounds to sulfuric acid is 4:1, the stirring temperature is 70–90°C, the stirring time is 11–13 h, the drying temperature after magnetic stirring is 70–90°C, the pyrolysis reduction temperature is 500–700°C, the pyrolysis reduction time is 1–3 h, and the drying temperature after washing is 90–110°C, and the drying time is 11–13 h.

[0013] In a preferred embodiment of the present invention, the soluble cobalt salt is Co(NO3)2·6H2O, the soluble copper salt is Cu(NO3)2·3H2O, and the soluble aluminum salt is Al(NO3)3·9H2O. The mass ratio of Co(NO3)2·6H2O to the volume ratio of water is 0.291g:90-100mL.

[0014] In a preferred embodiment of the present invention, the molar ratio of the soluble cobalt salt, the soluble copper salt, and the soluble aluminum salt is 1:1:1, and the molar ratio of divalent metal ions to trivalent metal ions in solution A is 2:1.

[0015] In a preferred embodiment of the present invention, the molar ratio of NaOH to Na2CO3 is 21:8.9, and the mass ratio of NaOH to water is 0.84g:90-100mL.

[0016] In a preferred embodiment of the present invention, the mass-to-volume ratio of the sulfur-doped coffee grounds biochar to solution A is 2g:90-100mL.

[0017] In a preferred embodiment of the present invention, the stirring temperature of the suspension is 65-85°C, the stirring time is 0.5-1.5h, the aging temperature is 65-85°C, and the aging time is 17-19h.

[0018] In a preferred embodiment of the present invention, the reducing atmosphere is a mixture of H2 and N2, wherein the volume ratio of H2 to N2 in the mixture is 1:9, and the mixed gas is a mixture of O2 and N2, wherein the volume ratio of O2 to N2 is 1:99.

[0019] Another object of the present invention is to provide a sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst prepared by any of the above preparation methods.

[0020] The third objective of this invention is to provide an application of the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst described above in the catalytic hydrogenation rearrangement of furfural to synthesize cyclopentanol. The application method is as follows: furfural is dissolved in H2O to obtain a mixed solution, and then the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst is added to the mixed solution and placed in a reaction vessel. The reaction is carried out at 140°C and 3.0 MPa H2 pressure. The ratio of furfural to H2O is 8 mmol:10 mL, and the ratio of the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst to furfural is 50 mg:8 mmol.

[0021] Compared with the prior art, the beneficial effects of the present invention are:

[0022] Biochar is a renewable carbon material that can be produced from renewable biomass such as rice husks, corn stalks, grapefruit peels, peanut shells, and walnut shells. Compared with other biomass, biochar extracted from coffee grounds generally has superior physicochemical properties. This is because during the roasting and preparation of coffee beans, molecules (such as caffeine, tannins, and polyphenols) escape and form uniformly distributed pores within the coffee grounds, which is beneficial for storing activators (such as H2SO4). This results in biochar materials with a higher specific surface area and pore volume. In addition, the surface of coffee grounds biochar activated with sulfuric acid is usually rich in oxygen-containing functional groups (such as -OH, -CO, -COOH, and -COO). - These functional groups (etc.) can serve as nucleation centers for LDH. In addition, after biochar is activated by sulfuric acid, sulfur atoms can be incorporated into the coffee grounds biochar framework (SCB). During heat treatment, strong metal-sulfur bonds can act as metal anchoring points, further enabling metal atoms to be well dispersed on the coffee biochar.

[0023] This invention uses an in-situ growth method to load Cu-Co-Al onto a coffee grounds biochar framework. Grafting Cu-Co-Al onto SCB promotes electron transfer from Cu to Co, leading to the formation of a Cu-Co alloy. There is a strong interaction between the two. The electronic interaction between Cu and Co is beneficial to the selective conversion of biomass furfural to cyclopentanol. During the catalytic reaction, it facilitates mass transfer and exposes more accessible active sites, thereby improving the catalytic performance of the catalyst. Attached Figure Description

[0024] Figure 1 XRD patterns of the samples: (a) SCB, (b) Cu-Al LDH / SCB, (c) Co-Al LDH / SCB, (d) Cu-Co-Al LDH / SCB; Symbols: LDH; (·)Amorphous carbon;

[0025] Figure 2 XRD patterns of the samples: (a) Cu-Al / SCB, Co-Al / SCB, Cu-Co-Al / SCB, and Cu-Co-Al; (b) magnified XRD patterns of Cu-Al / SCB, Co-Al / SCB, Cu-Co-Al / SCB, and Cu-Co-Al; Symbol: (ω) Cu 0 ;(*)Co 0 ;(◆)CuO;(◇)CuC2O4;(■)Cu-Co;(▲)CuCoO x ;

[0026] Figure 3The H2-TPR curves of the catalysts are shown. All catalysts were pretreated in situ at 400℃ for 2 h. (a) Cu-AlLDH / SCB, (b) Co-Al LDH / SCB, (c) Cu-Co-Al LDH / SCB, (d) Cu-Co-Al LDH.

[0027] Figure 4 Here are the scanning electron microscope images of (a) Cu-Co-Al / SCB; and the corresponding elemental diagrams of Cu, Co, Al, O, S, and C in (bg) Cu-Co-Al / SCB.

[0028] Figure 5 These are HRTEM images of Cu-Co-Al (a, b) and Cu-Co-Al / SCB (c, d) of the present invention;

[0029] Figure 6 The effect of different reaction conditions on the aqueous-phase hydrogenation rearrangement of furfural to cyclopentanol catalyzed by Cu-Co-Al / SCB was investigated. The reaction conditions were: 3.0 MPa H2; 140 °C; 8 mmol furfural; 10 mL H2O; 50 mg catalyst.

[0030] Figure 7 To illustrate the effect of different solvents on the Cu-Co-Al / SCB-catalyzed aqueous hydrogenation rearrangement of furfural to cyclopentanol, the bar charts for each solvent, from left to right, are FAL, FFA, CPO, CPL, and THFA; the reaction conditions are: 3.0 MPa H2; 140 °C; 8 mmol furfural; 10 mL H2O; 50 mg catalyst;

[0031] Figure 8 Arrhenius diagrams were created for the liquid-phase hydrogenation rearrangement of furfural to cyclopentanol catalyzed by Cu-Co-Al (a) and Cu-Co-Al / SCB (c) at different temperatures, as well as for the liquid-phase hydrogenation rearrangement reactions of Cu-Co-Al (b) and Cu-Co-Al / SCB (d). Reaction conditions: 3.0 MPa H2, 8 mmol furfural, 10 mL H2O, 50 mg catalyst, stirring rate (1000 rpm).

[0032] Figure 9 The hot filtration experiment of Cu-Co-Al / SCB catalyst was conducted under the following conditions: 3.0 MPa H2, 8 mmol furfural, 10 mL H2O, 140 °C, and 50 mg catalyst.

[0033] Figure 10For the recyclability test of Cu-Co-Al / SCB catalyst, the reaction conditions were: (a) 3.0 MPa H2, 8 mmol furfural, 10 mL H2O, 2 h, 140 °C, 50 mg catalyst; (b) 3.0 MPa H2, 8 mmol furfural, 10 mL H2O, 5 h, 140 °C, 50 mg catalyst.

[0034] Figure 11 To assess the long-term performance of Cu-Co-Al / SCB catalyzed liquid-phase hydrogenation rearrangement of furfural, the reaction conditions were: 3.0 MPa H2, 0.2 mmol / L furfural aqueous solution, feed rate 0.1 mL / min, gas flow rate 30 mL / min, 140 °C, and 0.5 g catalyst. Detailed Implementation

[0035] The following detailed description, in conjunction with embodiments of the present invention and accompanying drawings, provides a clear and complete illustration of the technical solutions in these embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0036] It should be noted that all technical terms used in this invention are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the following embodiments of this invention can be purchased from the market or prepared by existing methods.

[0037] Experimental materials

[0038] Coffee grounds were provided free of charge by Lucky Coffee Company (China). H2SO4 (98%) was purchased from Maclean's Biochemical Co., Ltd. High-purity H2 (99.999%) and N2 (99.999%) were provided by Henan Yuanzheng Special Gas Co., Ltd. Furfural was purchased directly from Aladdin Company. Copper nitrate trihydrate (Cu(NO3)2·3H2O, ≥99%), cobalt nitrate hexahydrate (Co(NO3)2·6H2O, ≥99%), and aluminum nitrate (Al(NO3)3·9H2O, ≥99%) were purchased from Maclean's Biochemical Co., Ltd. (Shanghai, China). Alcohols were purchased from Titan Technology Co., Ltd. (Shanghai, China). All chemicals were usable without further purification. Deionized water (DI) was used in all experiments. Other chemicals were purchased from China Pharmaceutical Chemical Co., Ltd. and were usable without further purification.

[0039] Example 1

[0040] A method for preparing a sulfur-doped coffee biochar-supported Cu-Co alloy catalyst includes the following steps:

[0041] (1) Preparation of sulfur-doped coffee grounds biochar (SCB):

[0042] 1g of dried coffee grounds was mixed with 5mL of sulfuric acid solution (the mass ratio of sulfuric acid to coffee grounds was 4:1). After magnetic stirring at 80℃ for 12h, the mixture was dried in an 80℃ constant temperature oven. The resulting material was then placed in a tube furnace and heated to 600℃ (heating rate 2℃·min) in a N2 environment (nitrogen flow rate 30mL / min). -1 The solid powder was calcined for 2 hours under the following conditions to obtain a solid powder. Finally, the obtained solid powder was washed with deionized water until neutral and dried at 100°C for 12 hours to obtain sulfur-doped coffee grounds biochar, denoted as SCB.

[0043] (2) Preparation of solution A:

[0044] Dissolve 1 mmol Co(NO3)2·6H2O, 1 mmol Cu(NO3)2·3H2O and 1 mmol Al(NO3)2·9H2O in 90 mL of deionized water and stir to obtain solution A;

[0045] (3) Preparation of solution B:

[0046] Solution B was obtained by dissolving 21 mmol NaOH and 8.9 mmol Na2CO3 in 90 mL of deionized water and stirring.

[0047] (4) Preparation of sulfur-doped coffee biochar-supported Cu-Co alloy catalyst

[0048] 2g of SCB was added to 90mL of solution A and stirred vigorously for 2 hours to obtain a mixed solution. Solution B was slowly added to the mixed solution containing solution A and SCB, and the mixture was stirred vigorously at room temperature to adjust the pH to 10.0, resulting in a suspension. The suspension was treated at 75℃ for 1 hour, and then aged at 75℃ without stirring for 18 hours. After aging, the precipitate was obtained by filtration and washed with distilled water until the pH of the filtrate reached approximately 7.0. The resulting filter cake was dried at 80℃ for 12 hours. Subsequently, the obtained catalyst was subjected to a reducing environment (H2 / N2 = 1 / 9, v / v) at 500℃ (heating rate: 2℃·min). -1 The catalyst was reduced for 2 hours under the following conditions, then cooled to room temperature, and then passivated for 2 hours with a mixed gas (O2:N2 = 1:99, v / v) to obtain a sulfur-doped coffee grounds biochar supported Cu-Co catalyst, named Cu-Co-Al / SCB.

[0049] Example 2

[0050] A method for preparing a sulfur-doped coffee biochar-supported Cu-Co alloy catalyst includes the following steps:

[0051] (1) Preparation of sulfur-doped coffee grounds biochar (SCB):

[0052] 1g of dried coffee grounds was mixed with 5mL of sulfuric acid solution (the mass ratio of sulfuric acid to coffee grounds was 4:1). After magnetic stirring at 70℃ for 11h, the mixture was dried in a 70℃ constant temperature oven. The resulting material was then placed in a tube furnace and heated to 500℃ (heating rate 2℃·min) in a N2 environment (nitrogen flow rate 30mL / min). -1 The solid powder was calcined for 3 hours under the following conditions. Finally, the obtained solid powder was washed with deionized water until neutral and dried at 90°C for 13 hours to obtain sulfur-doped coffee grounds biochar, denoted as SCB.

[0053] (2) Preparation of solution A:

[0054] Dissolve 1 mmol Co(NO3)2·6H2O, 1 mmol Cu(NO3)2·3H2O and 1 mmol Al(NO3)2·9H2O in 95 mL of deionized water and stir to obtain solution A;

[0055] (3) Preparation of solution B:

[0056] Solution B was obtained by dissolving 21 mmol NaOH and 8.9 mmol Na2CO3 in 95 mL of deionized water and stirring.

[0057] (4) Preparation of sulfur-doped coffee biochar-supported Cu-Co alloy catalyst

[0058] 2g of SCB was added to 95mL of solution A and stirred vigorously for 2 hours to obtain a mixed solution. Solution B was slowly added to the mixed solution containing solution A and SCB, and the mixture was stirred vigorously at room temperature to adjust the pH to 10.0, resulting in a suspension. The suspension was treated at 65℃ for 1.5 hours, and then aged at 65℃ without stirring for 19 hours. After aging, the precipitate was obtained by filtration and washed with distilled water until the pH of the filtrate reached approximately 7.0. The resulting filter cake was dried at 80℃ for 12 hours. Subsequently, the obtained catalyst was subjected to a reducing environment (H2 / N2 = 1 / 9, v / v) at 500℃ (heating rate: 2℃·min). -1 The catalyst was reduced for 2 hours under the following conditions, then cooled to room temperature, and then passivated for 2 hours with a mixed gas (O2:N2 = 1:99, v / v) to obtain a sulfur-doped coffee grounds biochar supported Cu-Co catalyst, named Cu-Co-Al / SCB.

[0059] Example 3

[0060] A method for preparing a sulfur-doped coffee biochar-supported Cu-Co alloy catalyst includes the following steps:

[0061] (1) Preparation of sulfur-doped coffee grounds biochar (SCB):

[0062] 1g of dried coffee grounds was mixed with 5mL of sulfuric acid solution (the mass ratio of sulfuric acid to coffee grounds was 4:1). After magnetic stirring at 90℃ for 13h, the mixture was dried in a 90℃ constant temperature oven. The resulting material was then placed in a tube furnace and heated to 700℃ (heating rate 2℃·min) in a N2 environment (nitrogen flow rate 30mL / min). -1 The solid powder was calcined for 1 hour under the following conditions to obtain a solid powder. Finally, the obtained solid powder was washed with deionized water until neutral and dried at 110°C for 11 hours to obtain sulfur-doped coffee grounds biochar, denoted as SCB.

[0063] (2) Preparation of solution A:

[0064] Dissolve 1 mmol Co(NO3)2·6H2O, 1 mmol Cu(NO3)2·3H2O and 1 mmol Al(NO3)2·9H2O in 100 mL of deionized water and stir to obtain solution A;

[0065] (3) Preparation of solution B:

[0066] Solution B was obtained by dissolving 21 mmol NaOH and 8.9 mmol Na2CO3 in 100 mL of deionized water and stirring.

[0067] (4) Preparation of sulfur-doped coffee biochar-supported Cu-Co alloy catalyst

[0068] 2g of SCB was added to 100mL of solution A and stirred vigorously for 2 hours to obtain a mixed solution. Solution B was slowly added to the mixed solution containing solution A and SCB, and the mixture was stirred vigorously at room temperature to adjust the pH to 10.0, resulting in a suspension. The suspension was treated at 85℃ for 0.5 hours, and then aged at 85℃ without stirring for 17 hours. After aging, the precipitate was obtained by filtration and washed with distilled water until the pH of the filtrate reached approximately 7.0. The resulting filter cake was dried at 80℃ for 12 hours. Subsequently, the obtained catalyst was subjected to a reducing environment (H2 / N2 = 1 / 9, v / v) at 500℃ (heating rate: 2℃·min). -1 The catalyst was reduced for 2 hours under the following conditions, then cooled to room temperature, and then passivated for 2 hours with a mixed gas (O2:N2 = 1:99, v / v) to obtain a sulfur-doped coffee grounds biochar supported Cu-Co catalyst, named Cu-Co-Al / SCB.

[0069] Comparative Example 1

[0070] A method for preparing a Cu-Co-Al catalyst includes the following steps:

[0071] (1) Dissolve 1 mmol Co(NO3)2·6H2O, 1 mmol Cu(NO3)2·3H2O and 1 mmol Al(NO3)2·9H2O in 90 mL of deionized water under stirring to obtain solution A;

[0072] (2) Dissolve 21 mmol NaOH and 8.9 mmol Na2CO3 in 90 mL of deionized water and stir to obtain solution B. Add solution B dropwise to solution A at room temperature while stirring vigorously until the pH is maintained at around 10.0. Treat the resulting suspension at 75 °C for 1 h, then age it at 75 °C for 18 h without stirring. After aging, filter the precipitate and wash it with distilled water until the pH of the filtrate reaches 7.0. Dry the resulting filter cake at 80 °C for 12 h, and then expose the material to a reducing environment (H2 / N2 = 1 / 9, v / v) at 500 °C (heating rate: 2 °C·min). -1 The catalyst was reduced for 2 hours under the given conditions, then cooled to room temperature, and then passivated for 2 hours with a mixed gas (O2:N2 = 1:99, v / v) to obtain the Cu-Co-Al catalyst, which was named Cu-Co-Al.

[0073] Comparative Example 2

[0074] A method for preparing a Cu-Al / SCB catalyst includes the following steps:

[0075] (1) Preparation of sulfur-doped coffee grounds biochar (SCB):

[0076] 1g of dried coffee grounds was mixed with 5mL of sulfuric acid solution (the mass ratio of sulfuric acid to coffee grounds was 4:1). The mixture was magnetically stirred at 80℃ for 12h, then dried in an 80℃ constant temperature oven. The resulting material was then placed in a tube furnace and heated to 600℃ (heating rate 2℃·min) in a N2 environment (nitrogen flow rate 30mL / min). -1 The solid powder was calcined for 2 hours under the following conditions to obtain a solid powder. Finally, the obtained solid powder was washed with deionized water until neutral and dried at 100°C for 12 hours to obtain sulfur-doped coffee grounds biochar, denoted as SCB.

[0077] (2) Dissolve 1 mmol Cu(NO3)2·3H2O and 1 mmol Al(NO3)2·9H2O in 90 mL of deionized water and stir to obtain solution A;

[0078] (3) Dissolve 21 mmol NaOH and 8.9 mmol Na2CO3 in 90 mL of deionized water and stir to obtain solution B. Add solution B dropwise to the suspension containing solution A and SCB at room temperature and stir vigorously until the pH is maintained at around 10.0. Treat the resulting suspension at 75 °C for 1 h, then age it at 75 °C for 18 h without stirring. After aging, filter the precipitate and wash it with deionized water until the pH of the filtrate reaches around 7.0. Dry the resulting filter cake at 80 °C for 12 h. Then, place the obtained material in a reducing environment (H2 / N2 = 1 / 9, v / v) at 500 °C (heating rate: 2 °C·min). -1 The catalyst was reduced for 2 hours under the following conditions. After the catalyst cooled to room temperature, it was passivated for 2 hours with a mixed gas (O2:N2 = 1:99, v / v) to obtain the Cu-Al / SCB catalyst, which was named Cu-Al / SCB.

[0079] Comparative Example 3

[0080] A method for preparing a Co-Al / SCB catalyst includes the following steps:

[0081] (1) Preparation of sulfur-doped coffee biochar (SCB):

[0082] 1g of dried coffee grounds was mixed with 5mL of sulfuric acid solution (the mass ratio of sulfuric acid to coffee grounds was 4:1). The mixture was magnetically stirred at 80℃ for 12h, then dried in an 80℃ constant temperature oven. The resulting material was then placed in a tube furnace under a N2 atmosphere (nitrogen flow rate 30mL / min) at 600℃ (heating rate 2℃·min). -1 Under the conditions of ) calcination for 2h, a solid powder was obtained. Finally, the obtained solid was washed with deionized water until neutral and dried at 100℃ for 12h to obtain sulfur-doped coffee grounds biochar, denoted as SCB.

[0083] (2) Dissolve 1 mmol Co(NO3)2·6H2O and 1 mmol Al(NO3)2·9H2O in 90 mL of deionized water and stir to obtain solution A;

[0084] (3) Dissolve 21 mmol NaOH and 8.9 mmol Na2CO3 in 90 mL of deionized water and stir to obtain solution B. Add solution B dropwise to the suspension containing solution A and SCB at room temperature and stir vigorously until the pH is maintained at 10.0. Treat the resulting suspension at 75°C for 1 h, then age it at 75°C for 18 h without stirring. After aging, filter the precipitate and wash it with deionized water until the pH of the filtrate reaches about 7.0. Dry the resulting filter cake at 80°C for 12 h. Then, place the obtained material in a reducing environment (H2 / N2 = 1 / 9, v / v) at 500°C (heating rate: 2°C·min). -1 The catalyst was reduced for 2 hours under the given conditions, then cooled to room temperature, and then passivated for 2 hours with a mixed gas (O2:N2 = 1:99, v / v) to obtain the Co-Al / SCB catalyst, which was named Co-Al / SCB.

[0085] Catalyst characterization

[0086] Kα-ray diffraction (XRD) analysis was performed in the 10°–75° range on a Rigaku D / MAX 2550VB / PC instrument. ICP-AES analysis was performed on a Varian ICP-710ES instrument. The sample was placed in a plastic beaker, mixed at 100°C for 4 h to dissolve the sample, and then diluted with water for detection. Temperature-programmed reduction (H2-TPR) was performed using a VDsorb-91i instrument. The catalyst was placed in a U-shaped quartz tube, and then pure Ar (10 mL·min) was added. -1 The sample was purged with H2 / Ar (10 mL·min⁻¹), pretreated at 400 °C for 1 h, and then cooled to room temperature. Afterwards, it was subjected to H2 / Ar (10 mL·min⁻¹) for purging. -1 Reduction (1 / 9, v / v) up to 900℃ (rate at 10℃·min) -1 Scanning electron microscopy (SEM) images were obtained on a GeminiSEM 500 using energy-dispersive X-ray spectroscopy (EDS).

[0087] Catalyst performance testing

[0088] The aqueous-phase hydrogenation rearrangement reaction of furfural was performed as follows: First, 8 mmol of furfural was dissolved in 10 mL of H2O. Then, 50 mg of the prepared catalyst was added to the mixture and placed in a 25 mL stainless steel autoclave equipped with a magnetic stirrer. The autoclave was then purged three times with N2 to displace the air, followed by three purgings with H2. Finally, H2 was added to a given pressure, and the mixture was heated to a specific temperature under magnetic stirring. After the reaction was complete, the catalyst was separated from the solution by filtration for subsequent analysis. The liquid product was qualitatively analyzed using an Agilent 6890 / 5973 gas chromatography-mass spectrometry system equipped with an HP-5MS column and a flame ionization detector (FID). For quantitative measurements, analysis was performed on a GC equipped with an FFAP capillary column, using 1-butanol as an internal standard. To assess the recyclability of the optimized catalyst, it was separated from the reaction mixture by filtration and then washed three times with ethanol. Finally, the obtained catalyst was dried at 80 °C for 1 h and then used in the next reaction. The conversion to the substrate was calculated as follows:

[0089]

[0090] The product selectivity and yield are calculated as follows:

[0091]

[0092]

[0093] Results Analysis

[0094] 1. Catalyst Characterization

[0095] First, N2 adsorption-desorption analysis was performed, and the BET specific surface area, pore volume, and average pore size of the samples were calculated based on the adsorption isotherms, summarized in Table 1. Compared with SCB, the LDH-derived catalyst has a lower BET specific surface area (Table 1, items 1-4). After loading Cu-Al, Co-Al, or Cu-Co-Al onto SCB, the BET specific surface area and pore volume remained almost unchanged compared to SCB (Table 1, items 1 and 5-7), indicating that loading Cu-Al, Co-Al, or Cu-Co-Al onto SCB did not significantly alter the structural properties of SCB. These results suggest that the structural performance of the LDH-derived catalyst supported on SCB is enhanced. Notably, the higher BET specific surface area and pore volume of SCB can promote mass transfer and expose more active sites during the catalytic reaction of the LDH-derived catalyst, thereby improving its catalytic performance. In addition, the contents of Cu and Co in the catalyst were determined by ICP-AES, as shown in Table 1. It can be found that the actual loading of Cu and Co is slightly different from the theoretical value. This may be due to the incomplete precipitation of different cations during the preparation of LDH precursor. The Cu / Co molar ratio in Cu-Co-Al and Cu-Co-Al / SCB is equal to the theoretical value (about 1.0), indicating that Cu-Co-Al can be successfully loaded onto SCB.

[0096] The XRD pattern of the sample is as follows Figure 1 and Figure 2 As shown, Figure 1 a shows the XRD pattern of SCB, with a broad diffraction peak (labeled ·) at 26.1°, corresponding to the (002) plane of amorphous carbon. After loading Cu-Al, Co-Al, or Cu-Co-Al LDH onto SCB, diffraction peaks corresponding to the LDH structure (labeled ·) can be detected. ()( Figure 1 bd), indicating that the LDH precursor was successfully loaded onto SCB. Subsequently, once the catalyst precursor was reduced, the characteristic layered structure of LDH disappeared in all samples. For Cu-Al / SCB ( Figure 2 a) Three new diffraction peaks (denoted as ω) can be clearly observed at 43.3°, 50.4°, and 74.1° (labeled ω), which is due to Cu 0 The diffraction patterns of the (111), (200), and (220) crystal planes (JCPDS 04-0836) reflect the good crystallinity of the formed copper. Furthermore, two weak peaks are observed at 38.8° and 46.5°, belonging to CuO (marked with ◆) (JCPDS 48-1548) and CuC2O4 (marked with ◇), respectively. For Co-Al / SCB ( Figure 2a) Two distinct diffraction peaks (marked as *) appeared at 44.2° and 51.5°, which can be attributed to Co. 0 Diffraction of (JCPDS15-0806). Figure 2 a and b show the newly reduced Cu-Co-Al / SCB catalyst. Notably, the characteristic peak (marked with ■) corresponding to the Cu-Co alloy is located at Cu... 0 With Co 0 between( Figure 2 b) This indicates that a Cu-Co alloy did indeed form on the Cu-Co-Al / SCB catalyst. Furthermore, the disappearance of the diffraction peaks for CuO and CuC₂O₄ in the Cu-Co-Al / SCB catalyst suggests that the introduction of Co promotes the reduction of Cu species. The broad peak around 36.6° can be attributed to CuCoO. x (Marked with ▲). CuCoO present on Cu-Co-Al / SCB x This may be due to oxidation of the Cu-Co alloy surface during XPS testing. For Cu-Co-Al catalysts, Cu remains on the Cu-Co-Al surface. 0 and Co 0 Diffraction peaks ( Figure 2 (a) and (b). Notably, no diffraction peaks corresponding to the Cu-Co alloy appeared in Cu-Co-Al, indicating that Cu-Co-Al loading on SCB can promote the formation of Cu-Co alloy sites. Furthermore, no diffraction peaks corresponding to Al2O3 appeared in all samples, suggesting that Al2O3 may exist in the MMO in an amorphous or highly dispersed form on the catalyst.

[0097] Table 1 Physicochemical properties of catalysts

[0098]

[0099]

[0100] The H2-TPR experiment investigated the interaction between Cu and Co elements, such as Figure 3 As shown in figure a, the Cu-Al LDH / SCB catalyst exhibits a reduction peak extending from 200 °C to 500 °C, which may be attributed to the reduction of Cu(II) to Cu. 0 For the Co-Al LDH / SCB catalyst, there are two reduction peaks located between 200 and 500 °C and between 600 and 900 °C, respectively. Figure 3b). The first reduction peak is related to the reduction of more easily reduced Co(II) present on the surface, while the second reduction peak (maximum value 780 °C) is the reduction of Co(II) elements that interact violently with SCB. On the other hand, the TPR curves of Cu-Co-Al LDH / SCB (reduction peak maximum values ​​340 °C and 525 °C) and Cu-Co-Al LDH catalyst (reduction peak maximum values ​​440 °C and 660 °C) also show two reduction peaks. Figure 3 c and d). The first reduction peak is due to the reduction of Cu(II) and Co(II) elements, which are more easily reduced on the surface, while the second reduction peak is attributed to the deep reduction of Co(II) elements. It is noteworthy that, compared with Co-Al LDH / SCB ( Figure 3 b) Compared to Cu-Co-Al LDH / SCB ( Figure 3 c) and Cu-Co-Al LDH ( Figure 3 d) The introduction of Cu can promote the reduction of surface Co(II) to Co. 0 This indicates a strong interaction between Cu and Co elements. Furthermore, it shows a strong interaction with Cu-Co-Al LDH (…). Figure 2 Compared to d), the reduction temperature of Co in Cu-Co-Al LDH / SCB is lower. Figure 3 c) indicates that the interaction between Cu and Co is stronger after Cu-Co-Al LDH is loaded onto SCB. Furthermore, H2-TPR studies show that Co may coexist in both metallic and oxidized states under pre-reduction conditions (500℃). Based on these results, it can be concluded that the strong interaction between Cu and Co elements in Cu-Co-Al / SCB not only promotes Co reduction but may also induce the formation of Cu-Co alloys, which is consistent with the XRD results.

[0101] EDS elemental diagram of Cu-Co-Al / SCB is as follows: Figure 4 As shown in Figure ag, it can be observed that Cu, Co, Al, O, and S are evenly distributed, with Cu and Co preferentially distributed together. Figure 4 bf) indicates that a Cu-Co alloy is likely formed in Cu-Co-Al / SCB, which is consistent with XRD ( Figure 1 and Figure 2 ) and H2-TPR ( Figure 3 The results of C( ). Furthermore, it is worth noting that C( Figure 4 The distribution of g) complements that of Cu, Co, Al, and O, further confirming that Cu-Co-Al was successfully grown in situ on the surface of SCB material and formed a close contact with SCB. Figure 4 The close contact between Cu-Co-Al and SCB can induce strong interactions between them, which is similar to H2-TPR (…). Figure 3 The results are consistent.

[0102] Next, HRTEM was used to resolve the spatial structure information of Cu-Co-Al and Cu-Co-Al / SCB catalysts, such as... Figure 5 As shown in the diagram, obvious Cu was found on the Cu-Co-Al. 0 Nanoparticles (NPs) and Co 0 The average size of the NPs is 12.4 nm. Figure 5 a). Figure 5 b shows the Co on the Cu-Co-Al catalyst. 0 (0.204nm) (111) plane and Cu 0 The (111) plane at (0.208 nm) is consistent with the XRD results. HRTEM images of the Cu-Co-Al / SCB catalyst are shown below. Figure 5 As shown in c and d. From Figure 5 c shows that Cu and Co elements are uniformly distributed on Cu-Co-Al / SCB, with an average size of 8.3 nm (mainly ranging from 7 to 10 nm). Figure 5 c) indicates that loading Cu-Co-Al onto SCB is beneficial for the uniform distribution of metal species, which is consistent with XRD ( Figure 1 and Figure 2 ) and EDS element diagram ( Figure 4 The results are consistent. Figure 5 In d, the lattice spacing of the Cu-Co alloy is 0.206 nm, which is consistent with the XRD results. Figure 2 b).

[0103] Based on the catalyst characterization described above, it can be seen that small nanoscale Cu-Co alloys are formed on Cu-Co-Al / SCB, and Cu-Co-Al and SCB form a close contact on Cu-Co-Al / SCB. The strong interaction between Cu and Co in Cu-Co-Al / SCB has been confirmed. The strong interaction between Cu and Co, as well as the geometric structure between Cu-Co-Al and SCB, can induce a large number of easily accessible Cu-Co alloy active sites, which helps to improve catalytic activity and selectivity.

[0104] 2. Catalyst performance evaluation

[0105] Various carbon-based catalysts were tested in the liquid-phase hydrogenation rearrangement of furfural. First, both the thermal blank experiment and SCB showed furfural conversion rates of <5% (Table 2, entries 1 and 2), indicating that the catalytic conversion of furfural requires the participation of a catalyst, and that SCB has almost no activity for furfural hydrogenation. With Cu-Al / SCB as the catalyst, the furfural conversion rate was 57.5%, with cyclopentanone and cyclopentanol as the main products, with selectivities of 48.2% and 37.9%, respectively (Table 2, entry 3). In addition, a small amount of furfuryl alcohol was formed (selectivity 6.5%), indicating that Cu-Al / SCB has low catalytic efficiency and selectivity for the conversion of furfural to cyclopentanol. Next, the aqueous-phase hydrogenation rearrangement of furfural was tested using Co-Al / SCB, achieving a furfural conversion rate of 70.3% and forming a greater number of products, including tetrahydrofuran (19.6% selectivity), cyclopentanone (9.5% selectivity), and cyclopentanol (63.9% selectivity) (Table 2, entry 4). It can be seen that the main byproduct when using Co-Al / SCB as a catalyst is tetrahydrofuran, because Co... 0 The hydrogenation sites showed no selectivity for the C=C and C=O double bonds in furfural. Considering the activity evaluations of Cu-Al / SCB and Co-Al / SCB, it was speculated that Cu-Co alloying might further promote the liquid-phase hydrogenation rearrangement of furfural to cyclopentanol; therefore, this invention prepared a Cu-Co-Al / SCB catalyst and applied it to the selective hydrogenation of furfural to cyclopentanol (Table 2, item 6). Cu-Co-Al / SCB exhibited complete furfural conversion and good selectivity (97.5%) for cyclopentanol. In contrast, the aqueous-phase hydrogenation rearrangement of the Cu-Co-Al catalyst was also tested, showing a furfural conversion of 78.6%, with cyclopentanol as the main product and a selectivity of 74.7%, and cyclopentanone as the main byproduct (with a selectivity of 22.3%), exhibiting low reactivity for the hydrogenation rearrangement of furfural to cyclopentanol (Table 2, item 6). These results indicate that the excellent catalytic performance of Cu-Co-Al / SCB can be attributed to the strong interaction between Cu and Co, which forms Cu-Co alloy active sites, thereby promoting the selective hydrogenation of furfural to cyclopentanol. Furthermore, Cu-Co-Al loaded onto SCB can further promote the conversion of furfural to cyclopentanol, possibly because Cu-Co-Al / SCB more readily exposes active sites compared to unsupported Cu-Co-Al, which is consistent with XRD (…). Figure 2 H2-TPR Figure 3 SEM-EDS maps Figure 4 ) and HRTEM Figure 5 The results are consistent.

[0106] Table 2 Catalytic performance of furfural on aqueous phase hydrogenation rearrangement on different catalysts

[0107]

[0108] Reaction conditions: 3.0 MPa H₂; 140 °C; 8 mmol furfural; 10 mL H₂O; 50 mg catalyst. Others: glycols, polymers, and other unknown products. All catalysts in Table 1 showed carbon yields exceeding 90% in the liquid products.

[0109] 3. Screening of reaction conditions

[0110] The aqueous-phase hydrogenation rearrangement of furfural to cyclopentanol was selected as a model reaction to screen the optimal reaction conditions for the Cu-Co-Al / SCB catalyst. Figure 6 ). Figure 6 'a' represents the effect of reaction temperature on the selective aqueous-phase hydrogenation rearrangement of furfural. As the temperature increases from 110℃ to 140℃, the furfural conversion rate increases from 80.8% to >99%. With the increase of reaction temperature, the selectivity of cyclopentanol gradually increases, reaching a maximum of 97.5% at 140℃. At the same time, as the temperature increases from 110℃ to 140℃, the selectivity of furfural alcohol gradually decreases from 91.3% to 0, indicating that furfural alcohol can be selectively produced at 110℃ and it is likely an important intermediate for the conversion of furfural to cyclopentanol.

[0111] The changes in furfural conversion and product distribution with reaction time during the selective hydrogenation of furfural catalyzed by Cu-Co-Al / SCB were investigated. Figure 6 As shown in b, in the initial stage of the reaction (0.5 h), the conversion rate of furfural reached 25.5%, reflecting the high catalytic activity of Cu-Co-Al / SCB. Furfuryl alcohol was the main product with a selectivity of 72.3%, while the selectivities of cyclopentanone and cyclopentanol were 18.2% and 8.5%, respectively. With further increase in reaction time, the conversion rate of furfural and the selectivity of cyclopentanol gradually increased, while the selectivities of furfuryl alcohol and cyclopentanone gradually decreased. At 5 h, the conversion rate of furfural was >99%, and the selectivity of cyclopentanol was 97.5%. These results clearly illustrate the tandem reaction pathway of furfural to cyclopentanol: furfural is first hydrogenated to furfuryl alcohol, then furfuryl alcohol undergoes a hydrogenation rearrangement reaction to produce cyclopentanone, and finally hydrogenated to the target product cyclopentanol.

[0112] The effect of H2 pressure on the catalytic performance of Cu-Co-Al / SCB catalysts is as follows: Figure 6 As shown in c. Under low pressure (0.2 MPa), cyclopentanone was the main product with a selectivity of 92.6%, and furfural conversion was 81.7%. Figure 5c) The high selectivity of cyclopentanone can be attributed to incomplete hydrogenation under low pressure. As the H2 pressure increased from 0.2 MPa to 3.0 MPa, the furfural conversion increased from 81.7% to >99%, and the cyclopentanol selectivity gradually increased from 4.1% to 97.5% as cyclopentanone (from 92.6% to 0) and furfuryl alcohol (from 3.3% to 0) were consumed. These results clearly demonstrate that the product selectivity can be controlled by adjusting the H2 pressure, i.e., selectively obtaining cyclopentanone (92.6% selectivity) under low pressure (0.2 MPa) and selectively obtaining cyclopentanol (97.5% selectivity) under high pressure (3.0 MPa).

[0113] Figure 6 The effect of furfural concentration on the catalytic performance of the Cu-Co-Al / SCB catalyst is described in section d. As the substrate concentration increased from 0.6 mol / L to 0.8 mol / L, furfural was completely converted, and the selectivity for cyclopentanol was >96%. When the furfural concentration increased from 0.9 mol / L to 1.1 mol / L, the furfural conversion and cyclopentanol selectivity decreased slightly. Based on these results, the optimal catalytic reaction conditions for the liquid-phase hydrogenation rearrangement of furfural to cyclopentanol in this invention are 140 °C, 5 h, 3.0 MPa H2, and 0.8 mol / L furfural aqueous solution.

[0114] 4. The effect of solvent

[0115] Solvents significantly influence reaction kinetics, catalytic activity, and selectivity. Under optimal reaction conditions, using Cu-Co-Al / SCB as a catalyst, the effects of different solvents on furfural conversion and product selectivity were investigated. Figure 7 As shown, the conversion rate of furfural in aprotic solvents, including toluene and n-hexane, using Cu-Co-Al / SCB as a catalyst is relatively low, which is likely related to the low solubility of furfural in these solvents. Notably, in non-aqueous solvents, the selectivity for cyclopentanol is consistently <8%, while furfuryl alcohol is the major product with a selectivity >86%, indicating that the selectivity of cyclopentanol is strongly dependent on the properties of the solvent. Various literature reports have demonstrated that furfural produces cyclopentanol via furfuryl alcohol intermediates. A key step involves the rearrangement of furfuryl alcohol to cyclopentanone during cyclopentanol production, a process that occurs only in H2O because H2O itself participates in the reaction. Conversely, when the reaction is carried out in non-aqueous solvents, the rearrangement reaction does not occur, and the furfuryl alcohol intermediate may be further hydrogenated to tetrahydrofurfuryl alcohol or pentanediol. These results suggest that the selectivity of furfuryl alcohol and cyclopentanol can also be adjusted by switching from non-aqueous to aqueous solvents when using Cu-Co-Al / SCB as a catalyst.

[0116] 5. Reaction Kinetics

[0117] The reaction mechanism of furfural's aqueous-phase hydrogenation rearrangement to cyclopentanol was thoroughly investigated through kinetic studies. It can be assumed that the selective hydrogenation of furfural follows a first-order reaction due to the extremely high amount of H2 (3.0 MPa H2). First, the reaction rates of the Cu-Co-Al catalyst at different temperatures (393-423 K) were collected, and its activation energy was calculated. Figure 8 a). According to the Arrhenius equation, the activation energy of the Cu-Co-Al catalyst is 76.5 kJ / mol ( Figure 8 b), while the activation energy of Cu-Co-Al / SCB is only 36.6 kJ / mol ( Figure 8 d) indicates that the activation energy of the Cu-Co-Al / SCB catalyst for aqueous hydrogenation rearrangement of furfural is lower than that of Cu-Co-Al. These results suggest that the Cu-Co-Al / SCB catalyst is more effective at activating substrate molecules than Cu-Co-Al. This is because SCB has a larger specific surface area, porosity, and sulfur-doped biochar sites, all of which are beneficial for dispersing Cu-Co-Al and exposing more readily accessible Cu-Co alloy active sites.

[0118] 6. Catalyst repeatability and stability

[0119] Through heat filtration experiment ( Figure 9 This ruled out the possibility that Cu-Co-Al / SCB was a homogeneous catalyst. After 2 hours of reaction, the catalyst was separated under hot filtration conditions. Figure 8 It can be seen that the reaction stops without a catalyst, but the furfural conversion rate increases significantly after the reintroduction of Cu-Co-Al / SCB. This result confirms the heterogeneity of Cu-Co-Al / SCB.

[0120] As is well known, recyclability is crucial for potential industrial applications. Therefore, this invention evaluates the recyclability of Cu-Co-Al / SCB-catalyzed aqueous-phase hydrogenation rearrangement of furfural. Figure 10 ).like Figure 10 As shown, the cyclopentanol yield remained almost constant in 9 repeated experiments (approximately 47% at 2h and approximately 97% at 5h), indicating that Cu-Co-Al / SCB exhibits good cycling stability for the catalytic aqueous hydrogenation rearrangement of furfural to cyclopentanol.

[0121] Subsequently, the long-term stability of Cu-Co-Al / SCB was also tested in a continuous reactor. Figure 11 As can be seen, with the increase of time (TOS = 90 h), the conversion rate of furfural remained >95%, and the selectivity of cyclopentanol remained >92%. These results indicate that Cu-Co-Al / SCB can serve as a stable and cost-effective heterogeneous catalyst for the aqueous hydrogenation rearrangement of furfural to cyclopentanol.

[0122] 7. Expand the substrate range

[0123] Subsequently, other important biomass (glycerol, levulinic acid, 5-hydroxymethylfurfural, guaiacol, and phenol) were used as substrates for the reaction, as shown in Table 3. Under Cu-Co-Al / SCB catalysis, glycerol was completely converted, with a selectivity of up to 88.5% for 1,2-propanediol (Table 3, entry 1). The conversion rate of levulinic acid was >99%, the selectivity of γ-valerol was >99% (Table 3, entry 2), and the selectivity of 5-hydroxymethylfurfural to 3-hydroxymethylcyclopentanol was 81.2% (Table 3, entry 3). Cu-Co-Al / SCB was also used for the hydrogenation of guaiacol (Table 3) and phenol (Table 3), with cyclohexanol as the main product and selectivities of 87.4% and >99%, respectively. These results indicate that Cu-Co-Al / SCB has high catalytic activity and selectivity for the hydrogenation of various platform molecules in biomass.

[0124] Table 3 shows the selective hydrogenation of various biomass-derived platform molecules on Cu-Co-Al / SCB.

[0125]

[0126]

[0127] Reaction conditions: 2 mmol substrate, 50 mg catalyst, 10 mL H2O, 3.0 MPa H2. All substrates showed complete conversion on Cu-Co-Al / SCB catalyst.

[0128] In summary, a sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst was successfully prepared via in-situ growth and applied to the aqueous hydrogenation rearrangement of furfural to cyclopentanol. The Cu-Co-Al / SCB catalyst exhibited complete furfural conversion and a cyclopentanol selectivity of 97.5%. Furthermore, the Cu-Co-Al / SCB catalyst demonstrated good recyclability, capable of at least nine cycles. Additionally, the Cu-Co-Al / SCB catalyst also exhibited high catalytic activity and selectivity for the hydrogenation of various biomass-derived platform molecules. The excellent catalytic performance of Cu-Co-Al / SCB is mainly attributed to the strong interaction between Cu and Co in the Cu-Co alloy. Moreover, the in-situ loading of Cu-Co-Al onto SCB facilitates mass transfer and exposes more readily accessible active sites (Cu-Co alloy sites). Therefore, this invention provides a potential solution for loading highly active LDH-derived alloy catalysts onto biochar materials, demonstrating its application potential in biomass conversion.

[0129] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. The application of a sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst in the catalytic hydrogenation rearrangement of furfural to synthesize cyclopentanol, characterized in that, The application method is as follows: Furfural is dissolved in H2O to obtain a mixed solution, and then the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst is added to the mixed solution and placed in a reaction vessel at 110~140°C. o The reaction was carried out under C and 0.2~3.0 MPa H2 pressure, wherein the ratio of furfural to H2O was 8 mmol:10 mL, and the ratio of the sulfur-doped coffee biocarbon supported Cu-Co alloy catalyst to furfural was 50 mg:8 mmol. The preparation method of the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst includes the following steps: Coffee grounds were mixed with sulfuric acid, stirred and dried, and then pyrolyzed and reduced in an inert atmosphere to obtain a solid powder. The solid powder was washed and dried to obtain sulfur-doped coffee grounds biochar. Soluble cobalt salt, soluble copper salt, and soluble aluminum salt are dissolved in water and mixed with stirring to obtain solution A. NaOH and Na2CO3 are dissolved in water and mixed with stirring to obtain solution B. The sulfur-doped coffee biochar was added to solution A and stirred to obtain a mixed solution. Solution B was added to the mixed solution to adjust the pH to 9-11, resulting in a suspension. The suspension was heated and stirred and aged. The precipitate was obtained by filtration. The precipitate was filtered and washed until the filtrate was neutral to obtain a filter cake. The filter cake was dried and then thermally reduced in a reducing atmosphere. After cooling to room temperature, it was passivated with a mixed gas to obtain a sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst.

2. The application of the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst according to claim 1 in the catalytic hydrogenation rearrangement of furfural to synthesize cyclopentanol, characterized in that, In the preparation of sulfur-doped coffee grounds biochar, the mass ratio of coffee grounds to sulfuric acid is 4:1, the stirring temperature is 70-90 °C, the stirring time is 11-13 h, and the drying temperature after stirring is 70-90 °C. o C, the pyrolysis reduction temperature is 500~700 o C, the pyrolysis reduction time is 1~3 h, and the drying temperature after washing is 90~110℃. o C, drying time is 11~13 h.

3. The application of the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst according to claim 1 in the catalytic hydrogenation rearrangement of furfural to synthesize cyclopentanol, characterized in that, The soluble cobalt salt is Co(NO3)2·6H2O, the soluble copper salt is Cu(NO3)2·3H2O, and the soluble aluminum salt is Al(NO3)3·9H2O. The mass ratio of Co(NO3)2·6H2O to the volume ratio of water is 0.291 g: 90~100 mL.

4. The application of the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst according to claim 1 in the catalytic hydrogenation rearrangement of furfural to synthesize cyclopentanol, characterized in that, The molar ratio of the soluble cobalt salt, soluble copper salt, and soluble aluminum salt is 1:1:1, and the molar ratio of divalent metal ions to trivalent metal ions in solution A is 2:

1.

5. The application of the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst according to claim 1 in the catalytic hydrogenation rearrangement of furfural to synthesize cyclopentanol, characterized in that, The molar ratio of NaOH to Na2CO3 is 2:

1. 8.9, The mass ratio of NaOH to water is 0.84 g: 90~100 mL.

6. The application of the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst according to claim 1 in the catalytic hydrogenation rearrangement of furfural to synthesize cyclopentanol, characterized in that, The mass-to-volume ratio of the sulfur-doped coffee grounds biochar to solution A is 2 g: 90~100 mL.

7. The application of the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst according to claim 1 in the catalytic hydrogenation rearrangement of furfural to synthesize cyclopentanol, characterized in that, The stirring temperature of the suspension is 65~85°C. o C, the stirring time is 0.5~1.5 h, and the aging temperature is 65~85℃. o C, aging time is 17~19 h.

8. The application of the sulfur-doped coffee grounds biochar-supported Cu-Co alloy catalyst according to claim 1 in the catalytic hydrogenation rearrangement of furfural to synthesize cyclopentanol, characterized in that, The reducing atmosphere is a mixture of H2 and N2, with a volume ratio of H2 to N2 of 1:

9. The mixed gas is a mixture of O2 and N2, with a volume ratio of O2 to N2 of 1:99.

Citation Information

Patent Citations

  • Carbon fiber compound nano copper cobalt alloy catalyst for low-carbon alcohol synthesis and preparation method of catalyst

    CN104549283A

  • Preparation method and application of heteroatom-doped biochar

    CN117623302A